Un descanso a la “locura” : La emergencia del trastorno de estrés postraumático en los veteranos de la Segunda Guerra Mundial en EE.UU. y la lobotomía como solución desesperada (2015)
ABSTRACT: World War II marked the beginning of the scientific understanding of mental disorders arising conflicts. It also witnessed the clash between scientific truths of every age around the same psychological symptoms, emerging from different wars. This article will show efforts from the scientific field to get to the real reason for the symptoms currently associated with PTSD, to end stigma of weakness how to cause PTSD. But while this was taking place, the way to reach an effective treatment against this phenomenon was full of obstacles and mistakes that hurt veterans who underwent these procedures in all areas making up everyday life. One of the most famous was the lobotomy procedures and resulted in the appearance of recurrent complaints from the family responsible for authorizing surgery, expression of repentance and controversial opinions in the medical and scientific circle until his disappearance of antipsychotic drugs in the century XX.